Non-puerperal Acute Uterine Inversion - Sarkar, M; Roy, D; Mondal, J; Halder, M; Ghosh, RM; Ghosh, BK (Nepal Journal of Obstetrics and Gynaecology, 2014)
Non-puerperal acute inversion of uterus is a rare complication that occurs as a complication of intra uterine tumors, especially big sub mucous leiomyoma. It is so rare that many gynecologists may not encounter such a case in their life time professional carrier. This condition causes severe pain, vaginal bleeding and shock. Management consists of manual reposition through cervical ring or surgical corrective measures. We report a case of acute uterine inversion in a 42 years lady due to big sub mucous fibroid. This case was initially managed by vaginal myomectomy then uterus was repositioned by Haultain’s technique, which was abdominal hysterectomy. DOI: http://dx.doi.org/10.3126/njog.v9i1.11190 NJOG 2014 Jan-Jun; 2(1):58-60